2019
DOI: 10.1186/s12879-019-3714-z
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the virulence genes and antibiotic susceptibility patterns of Vibrio cholerae O1 in environmental and clinical isolates in Accra, Ghana

Abstract: BackgroundCholera has been endemic in Ghana since its detection in 1970. It has been shown that long-term survival of the bacteria may be attained in aquatic environments. Consequently, cholera outbreaks may be triggered predominantly in densely populated urban areas. We investigated clinical and environmental isolates of Vibrio cholerae O1 in Accra to determine their virulence genes, antibiotic susceptibility patterns and environmental factors maintaining their persistence in the environment.MethodsWater samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 38 publications
4
18
0
1
Order By: Relevance
“…Nevertheless, there were few 2014 outbreak genotypes that persisted in 2015 signifying the inefficiency of the control measures put in place or existence of an unknown environmental reservoir. This data agrees with findings of Eibech et al [34] and Abana et al [50], which suggested a potential reservoir in the environment. Interestingly, the clustering pattern by MLVA was very different from the clonal distribution derived from the presence/absence of specific virulent factors (Figs 3 and 4).…”
Section: Plos Onesupporting
confidence: 93%
See 1 more Smart Citation
“…Nevertheless, there were few 2014 outbreak genotypes that persisted in 2015 signifying the inefficiency of the control measures put in place or existence of an unknown environmental reservoir. This data agrees with findings of Eibech et al [34] and Abana et al [50], which suggested a potential reservoir in the environment. Interestingly, the clustering pattern by MLVA was very different from the clonal distribution derived from the presence/absence of specific virulent factors (Figs 3 and 4).…”
Section: Plos Onesupporting
confidence: 93%
“…[ 34 ] and Abana et al . [ 50 ], which suggested a potential reservoir in the environment. Interestingly, the clustering pattern by MLVA was very different from the clonal distribution derived from the presence/absence of specific virulent factors (Figs 3 and 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similar trends have also been reported from other studies in Ghana (Abana et al, 2019) and Nepal (Shrestha et al, 2015). Similarly nalidixic acid showed 100% resistance to both clinical and environmental isolates in Kathamandu city in Nepal (Greenland et al, 2016) and South America (Abana et al, 2019). Resistance patterns of antibiotics in V. cholerae are known due to rapidly fluctuation in nature, which unstably carry plasmids that confer resistance and the absence of selective pressure from antibiotics which naturally resides in the organisms in the aquatic environment to the organisms.…”
Section: Discussionsupporting
confidence: 84%
“…Therefore, many bacterial virulence factors (VFs) are easily spread in bacterial populations by horizontal gene transfer, converting mutualistic or commensal bacteria into potential opportunistic pathogens. Several examples of virulent (and highly virulent) and multiresistant disseminated clones have already been reported throughout the literature (8–10; for a review, see reference 11).…”
Section: Introductionmentioning
confidence: 99%